2006
DOI: 10.1007/s11904-006-0012-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid HIV testing: A review of the literature and implications for the clinician

Abstract: HIV counseling and testing services are critical for individuals to access HIV prevention and treatment. Unfortunately, the standard HIV testing algorithm is complex and includes the use of a sensitive enzyme immunoassay (EIA), followed by a Western blot if the EIA is positive. This process can take 1 week or longer. Therefore, innovative approaches that incorporate simpler diagnostic algorithms are needed to reach the large number of individuals who are not aware that they are HIV-infected. Currently availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 39 publications
0
41
1
1
Order By: Relevance
“…The use of rapid HIV tests has now become routine in many areas of the world due to their simplicity, low cost, and excellent performance characteristics (8,24). In the United States, six rapid HIV assays are now approved by the U.S. Food and Drug Administration, and four of these have been categorized as "waived" testing under CLIA 1988, where the qualifications of the testers are minimal.…”
Section: Discussionmentioning
confidence: 99%
“…The use of rapid HIV tests has now become routine in many areas of the world due to their simplicity, low cost, and excellent performance characteristics (8,24). In the United States, six rapid HIV assays are now approved by the U.S. Food and Drug Administration, and four of these have been categorized as "waived" testing under CLIA 1988, where the qualifications of the testers are minimal.…”
Section: Discussionmentioning
confidence: 99%
“…They are simple to use and have high specificity, however, false positives do occur and they have been criticised in previous years for lacking in sensitivity relative to reference enzyme immunoassays (EIA/ELISA), particularly during primary HIV infection and infection by variant strains (Makuwa et al, 2002). There is, however, research evidence to indicate that rapid HIV tests produce results of comparable sensitivity and specificity to the ELISA test (Franco-Paredes et al, 2006;Greenwald et al, 2006;Branson, 2000a). Laboratory testing of 1266 specimens at rural peripheral laboratories of varied combinations of seven rapid HIV tests even showed a specificity of 100% (Stetler et al, 1997).…”
Section: Diagnostic Accuracy Of Hiv Rapid Testsmentioning
confidence: 99%
“…Debattista et al, 2007;Hamers et al, 2008;Delaney et al, 2006). Independent performance data for 4 FDA approved rapid HIV tests (Franco-Paredes et al, 2006) and a wider range of rapid tests (Branson, 2000a) highlight product testing with both sensitivity and specificity outcomes of 100% (Oraquick and Retrocell HIV-1/2) (Branson, 2000a). Data from 2006 showed that in testing, sensitivity and specificity exceeded 99% in 4 FDA approved tests (with the exception of Reveal G2 Plasma test where specificity is 98.6%) (Franco-Paredes et al, 2006).…”
Section: Diagnostic Accuracy Of Hiv Rapid Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…This panel can serve a key function for the evaluation of antibody tests because it allows different HIV-specific antibody tests to be assessed for their sensitivities with specimens that may have relatively low anti-HIV immunoglobulin G (IgG) titers or that may contain only IgM. Previous studies have evaluated the sensitivities of various rapid tests, including analyses with seroconversion panels (1,5,8,10,12,16,19). However, no work to date has comprehensively evaluated the performance characteristics of all FDA-approved devices.…”
mentioning
confidence: 99%